Atlantic republic : the American tradition in English literature - Giles, Paul (OUP E-Books., 2006)
Giles describes a tradition of English literary figures since 1776 who have either emigrated to the United States or whose writing has been shaped by American ideas. The writers discussed here include Lord Byron, Charles Dickens, D.H. Lawrence, P.G. Wodehouse, and Angela Carter.